DAMPAK SOSIAL EKONOMI DAN BUDAYA OBJEK WISATA SUNGAI HIJAU TERHADAP MASYARAKAT DI DESA SALO KECAMATAN SALO KABUPATEN KAMPAR - Rahmah, Winda; ", Nurhamlin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
This research was conducted in Desa Salo Kecamatan Salo Kabupaten Kampar. The purpose of this study was to identify the profile attractions sungai hijau di Desa Salo Kecamatan Salo Kabupaten Kampar. The research titled “Impact of Socio economic and Cultural Community Attractions Sungai Hijau in Desa Salo Kecamatan Salo Kabupaten Kampar”. Topics focus of this research is the socio-economic impact and cultural Community attractions Sungai Hijau in Desa Salo Kecamatan Salo Kabupaten Kampar. The sample in this study amounted to 67 people. The author uses descriptive quantitative method and the data were analyzed quantitatively and using the decision-stratified sampling technique. Instruments of data are observation, questionnaires and documentation. From research conducted, the authors found that Attractions Sungai Hijau mpact either directly or indirectly on people's lives Desa Salo. The resulting impact is: the impact of economic and social impacts. With the opening Attractions Sungai Hijau and managed by the community Desa Salo jointly provide economic impact on the community one is opening up new job opportunities for people who previously did not have a job. He opened Attractions Sungai Hijau directly contributed to the increase in incomes of the population Desa Salo. The opening of new jobs since Attractions Sungai Hijau means the largest contribution to the decrease in the number of unemployment in Desa Salo. People's habits change with the rise and development of Attractions Sungai Hijau as a preferred tourist destination bustling audience. Changes in social values is felt by the public because the number of socio-cultural values brought by various visitors. The diversity of socio-cultural values that visitors a spectacle for young people who are still in the stage of developments the search for identity. Keywords: Tourist attraction Sungai Hijau, Social Economic Impact